Summa imaginaries Romaniae - Liliana Danciu (Incursiuni în imaginar, 2021)
Under the general coordination of the university professor Corin Braga, towards the end of 2020, it appears at the Polirom Publishing House ”The Encyclopedia of Imaginaries in Romania”, a collective volume to which teachers of the faculties of the “Babeș Bolyai” University from Cluj-Napoca contributed. The work is structured in five large and dense volumes, thematically designed on a certain type of imaginary (literary, linguistic, historical, religious, artistic), each under the distinct coordination of a specialist in the field: Corin Braga, Elena Platon (with the expertise of the scientific consultant Gheorghe Chivu, corresponding member of the Romanian Academy), Sorin Mitu, Ioan Chirilă, Liviu Malița. The creation of an encyclopedia of imaginaries in the Romanian cultural space is a major and necessary scientific project for (re) articulating the identity profile of Romanian culture, understanding and assuming its place and role in the European and global space. Romanian imaginaries - literary, linguistic, historical, religious, artistic - are approached by the authors of numerous chapters of the Encyclopedia in an interdisciplinary manner, as "fluid forms of heritage and vectors of identity circumscription." Through an extensive collective research of comparative synthesis analysis, with interdisciplinary character, this work in five volumes becomes a true Summa imaginaries Romaniae. The five volumes become as many semantic basins that are based on the imaginary of an individual (creator of the work) and of Romanian society, in different stages and stages of history and culture, respectively a complex universe of ideas and representations about self and world, concepts and mentalities. , myths, beliefs and ideologies. The extensive collective work is an innovation in the Romanian academic space under at least two aspects: it offers a unique tool of analysis on Romanian culture and encourages future research to overcome the rigidity of certain theoretical patterns, in favor of a dynamic and "fluid" vision. The research on the imaginary is a tradition in the "Phantasma" Center, founded and led by university professor Corin Braga. He and the members have published individual papers, in the country and abroad, contribute articles in the bi-annual magazine "Echinox", organize international conferences and congresses on the subject of the imaginary. This impressive Summa of the imaginaries in Romania, in the realization of which only researchers from the “Babeș Bolyai” University of Cluj-Napoca were involved, proves that this type of research has become a real academic phenomenon.